Dinamika Politik Menuju Pemilihan Presiden 2024 di Indonesia: Studi Social Network Analysis - Prakoso, Bayujati; Illahi, Fajar Kurnia; Himmah, Rif’atul (Fakultas Ilmu Sosial dan Ilmu Politik Unwahas, 2023)
The study aims to see the dynamics that occur ahead of the 2024 Presidential Election in Indonesia. This research methods is qualitative approach, using bibliometric analysis and Social Network Analysis (SNA). The results of the analysis in this study show that there are political figures who emerged, namely Muhaimin Iskandar, Anies Baswedan, Ganjar Pranowo, and Puan Maharani. Muhaimin Iskandar was narrated as a suitable person as a presidential candidate by inviting the public to support PKB and NU residents to support Muhaimin Iskandar. Anies Baswedan, who received support from the audience (a figure who was seen as bringing concrete change and a sincere person), and some questioned the faction that was seen as too early to support Anies, until information about Anies eating babi guling was proven to be false information. Meanwhile, Ganjar figures that in network analysis on Netlytic, the @ganjaranapp account did not display information but instead got the status of a suspended account from Twitter. Puan is narrated as a popular woman. On the other hand, there is a persuasive narrative of succeeding the 2024 Presidential Election as a democratic practice in the spirit of the 1998 Reform. In addition, we are reviewing issues that may arise ahead of the 2024 Presidential Election: the issue of the 20% Presidential Threshold, the publication of media information that allows raising the issue of COVID-19, the politics of SARA, and the issue of moving Ibu Kota Nusantara.